Effects of music on the preoperative and intraoperative anxiety through the assessment of pupil size and vital signs (blood pressure, respiratory, and pulse rates) among cataract surgery patients at UNTH-Enugu - Ezepue, Chukwubuike Obiora; Anyatonwu, Obinna Princewill; Duru, Christian Chukwuka; Odini, Franklin; Nwachukwu, Nkiru Zuada; Onoh, Chidimma; Nwachukwu, Nwamaka; Oguonu, Chukwunonso Afam (Frontiers in Ophthalmology, 2024)
Background/Aim: To examine how music can impact pre-operative and intraoperative anxiety via assessment of physiological markers such as pupil size, blood pressure, pulse rate and respiratory rate. Methods: This is a randomized interventional study of individuals aged 50 years and above who were scheduled for and undergoing cataract surgery under regional anaesthesia, with music (test group) randomly matched with similar individuals undergoing the same procedure but without music (control group). The surgeries were performed at the Ophthalmology theatre of the University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla, Enugu. Using a systematic random sampling method, a total of 98 patients were selected into two groups. Both groups completed the STAI Questionnaire at baseline, immediately on entrance into the preoperative room and 5minutes after intervention. Relevant study indices (blood pressure, pulse, respiratory rate and pupil diameter) were measured and recorded, and these served as baseline parameters. The State Trait Anxiety Inventory questionnaire (STAI) was then administered. Results were analyzed using the SPSS version 20 and Analysis of Variance was This is a provisional file, not the final typeset article used to compare means of variables measured at baseline, preoperative before intervention and preoperative after intervention. Categorical variables were compared using the Chi-square test. Student T-test was used to analyze the continuous variables. Results: Our analysis using the multiple linear regression, showed that music has an effect on preoperative anxiety and intraoperative anxiety by positively affecting the blood pressure, pulse rate, respiratory rate and pupil diameter (P≤0.001). Conclusion: Music reduces preoperative and intraoperative anxiety evidenced by its effect on the physiological biomarkers.